+0  
 
0
263
1
avatar

8i^-6?

Guest May 31, 2017
 #1
avatar+17744 
+3

Some background:  i2 = -1     i4 = 1     i8 = (i4) · (i4)  = 1 · 1 = 1

 

8 · (i-6

Multiply by  i8  (which is just 1):  8 · (i-6) · i8  =  8 · i2  =  8 · -1  =  -8

geno3141  May 31, 2017

9 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.